Fostering Noble Morals Through Example and Habituation (Case Study at TPA At-Thususniah) - Asmawati, Diah; Aziz, Ikhwan; Wijaya, Adi (Assyfa Journal of Islamic Studies, 2024)
Noble morals are commendable behavior that is important for every community to know, practice and get used to. Based on this, the problem in this research is that at At-Thusuniah TPA there are still children who do not respect their parents, speak less politely, and behave less well towards their peers. Based on these problems, the aim of writing this article is to describe the development of noble morals through example and habituation at At-Thusuniah TPA. The method used in this research is qualitative field. Data collection methods use observation, interviews and documentation. The data source uses primary data sources originating from TPA ustadzah, TPA santri, TPA walisantri, and secondary data sources originating from journals or data related to research. The validity of the data uses triangulation of sources and techniques. The data analysis technique uses data reduction, data presentation, and data verification. The results of this research include the implementation of moral development at the At-Thusuniah TPA which is implemented in the activities at the TPA through example and habituation. 1) the exemplary methods of the ustadzah at TPA include discipline (wearing polite clothes, sitting orderly when reciting the Koran, throwing rubbish in the right place, obeying orders), good manners (saying greetings, respecting each other), social relations (saying goodbye, saying goodbye a by raising both hands, greeting each other, the etiquette of calling a friend). 2) habituation methods include discipline (leaving on time, praying before studying, memorizing short surahs and daily prayers, being orderly when studying), manners (getting used to saying thank you, sitting when eating and drinking), social relationships (forgiving each other fellow friends). The urgency of moral development at TPA is to form the personality of students who are devout, have noble character and are virtuous.